Advanced age enhances the sepsis-induced up-regulation of the γ- and α7-nicotinic acetylcholine receptors in different parts of the skeletal muscles. (July 2016) - Xie, Fei; Min, Su; Liu, Li; Peng, Lihua; Hao, Xuechao; Zhu, Xianlin
Highlights: Dysfunction of skeletal muscles in elderly people may associate with the up-regulation of γ- and α7-nAChR. Advanced age can aggravate the sepsis-induced up-regulation of the γ- and α7-nAChR. The diaphragm expressed a higher number of γ- and α7-nAChR in sepsis. Muscle weakness in old age and sepsis may have common molecular underpinnings (neuregulin-1-ErbB pathway). Abstract: Background: The muscle mass decreases with age, leading to frailty and weakness; however, the role of acetylcholine receptors in this process has not been properly studied. In this article, we hypothesize that diaphragmatic as well as peripheral muscle weakness may be caused by the up-regulation of gamma and alpha 7 nicotinic acetylcholine receptors (nAChRs) on muscle cell membranes. Method: Adult male rats were randomly divided into sham and sepsis groups. Sepsis was induced by cecal ligation and puncture (CLP). Blood specimens and biopsies of tibialis anterior muscle and diaphragm were obtained at 24 h post CLP. Results: Up-regulation of gamma and alpha 7 nAChRs was detected in both sham and septic groups; however, this response was more robust in septic animals. Compared to tibialis anterior muscle, the diaphragm expressed a higher number of both receptor types. Conclusions: Muscle weakness in old age and sepsis may have common molecular underpinnings. Loss of diaphragmatic strength may explain hypoxia and respiratory failure often encountered in frail elderly.